Molecular dynamics investigation of ivermectin bound to importin alpha/beta heterodimer. Issue 4 (4th March 2022) - Sultana, Mossammad U. C.; Uddin, Md. Giash; Hossain, Md. Billal; Ali, Md Ackas; Sonia, Zannatul Ferdous; Kamal, Suprio; Halim, Mohammad A.
ABSTRACT: Ivermectin (D1), an FDA-approved drug, is mainly used as an inhibitor for the treatment of parasitic infections. This drug was drawn attention due to its effectiveness in COVID-19 treatment. In this work, we investigated how ivermectin and its analogues are interacted with Impα/β1 heterodimer by molecular docking, steered molecular dynamics (SMD), classical molecular dynamics (MD), and MM/PBSA binding free energy analysis. Docking results showed that ivermectin dimer showed the highest binding affinity of −12.2 kcal/mol compared to its monomer. In SMD, the highest acceleration of 600 pm/ps 2 is noticed for D1-Impα/β1 complex in the distance from 18.27 to 18.36 Å. The pulling force of 1745.86 pN is also detected for D1-Impα/β1. To validate the docking and SMD results, 100 ns molecular dynamics (MD) simulation is performed on the D1-Impα/β1 complex. The average RMSD value indicates a good structural stability of the complex despite some significant changes at the beginning. It is noted that most of the residues are stable over the simulation time with an average RMSF value of less than 2.65 Å. The MM/PBSA free energy of ivermectin also shows strong and spontaneous binding with the Impα/β1. GRAPHICAL ABSTRACT: UF0001